Pepper Fruit Elongation Is Controlled by Capsicum annuum Ovate Family Protein 20 - Borovsky, Yelena; Raz, Amit; Doron-Faigenboim, Adi; Zemach, Hanita; Karavani, Eldad; Paran, Ilan (Frontiers in Plant Science, 2022)
Fruit shape is one of the most important quality traits of pepper (Capsicum spp.) and is used as a major attribute for the classification of fruit types. Wide natural variation in fruit shape exists among the major cultivated species Capsicum annuum, allowing the identification of several QTLs controlling the trait. However, to date, no genes underlying fruit shape QTLs have been conclusively identified, nor has their function been verified in pepper. We constructed a mapping population from a cross of round- and elongated-fruited C. annuum parents and identified a single major QTL on chromosome 10, termed fs10, explaining 68% and 70% of the phenotypic variation for fruit shape index and for distal fruit end angle, respectively. The QTL was mapped in several generations and was localized to a 5 Mbp region containing the ortholog of SlOFP20 that suppresses fruit elongation in tomato. Virus-induced gene silencing of the pepper ortholog CaOFP20 resulted in increased fruit elongation on two independent backgrounds. Furthermore, CaOFP20 exhibited differential expression in fs10 near-isogenic lines, as well as in an association panel of elongated- and round-fruited accessions. A 42-bp deletion in the upstream region of CaOFP20 was most strongly associated with fruit shape variation within the locus. Histological observations in ovaries and fruit pericarps indicated that fs10 exerts its effect on fruit elongation by controlling cell expansion and replication. Our results indicate that CaOFP20 functions as a suppressor of fruit elongation in C. annuum and is the most likely candidate gene underlying fs10.